A diagnostic intoxication tool for clozapine and phenytoin using hybrid micelle liquid chromatography. Issue 1 (1st January 2021) - Ayman, Aya; EL-Shabrawy, Yasser; Zeid, Abdallah M.; Wahba, M. E. K.
Abstract : Micellar liquid chromatography was employed for the quantification and separation of the antidepressant drug clozapine (CLZ) and antiepileptic agent phenytoin (PHY). This mixture was separated using C8 column operating at 40°C using a mobile phase consisting of 0.075 M sodium dodecyl sulphate (SDS), 10% acetonitrile, 0.3% triethylamine (TEA), adjusted to pH 2.5 by 2 M ortho-phosphoric acid and applying a simple gradient program starting with a flow rate of 0.8 mL/min for the first 10 min of analysis applying 220 nm as detection wavelength, followed by raising the flow rate to 1.5 mL/min till end of analysis, adopting UV detection wavelength of 250 nm. The proposed method was used to quantify the concentration of both (CLZ) and (PHY) in rat whole blood whether spiked or in vivo suggesting its utility as a diagnostic tool for intoxication with either drugs in emergency rooms.